THE FLOUTING MAXIMS IN “THE LORAX” MOVIE SCRIPT - -, ABIDAH (Jurnal Ilmiah Mahasiswa FIB, 2013)
To make a good communication, human must follow certain principles. That is why, Grice offers to use theory of cooperative principle to avoid misunderstanding and misinterpretation between the speaker and the listener. However, some people do not fulfill those maxims to be used in the conversation for certain reasons, and when they violate the maxims it is called flouting maxims. A descriptive qualitative approach is used for this study because the data are in the form of words rather than of numbers and statistics. This study reveals that based on Grice’s Cooperative theory, there are three maxims which are flouted by the characters of “The Lorax” movie. Those flouting maxims are flouting maxim of quality, flouting maxim of quantity, and flouting maxim of relation. And the intended meaning of flouting maxims in this movie are not difficult to be understood. Keywords: Flouting Maxims, The Lorax Movie Script